EKSPLORASI LIMBAH KACA PADA PROSES FINISHING GELASIR BODI KERAMIK - Arif Suharson (Corak : Jurnal Seni Kriya, 2017)
Currently, industrial waste is an important issue since it is associated to global warming. Glass is used in such kinds of products as perfume and beverage bottles and lamps. Glass is preferred due to its advantage of transparency. However, glass also has disadvantage of fracture. More importantly, glass is non-biodegradable substance and therefore it contaminates the earth. Thus, besides plastic waste, glass waste is a serious issue and deserves comprehensive treatment to prevent natural sustainability. It takes one billion years to have the glass degradable naturally,The researcher is interested in researching glass waste. It is expected that the study will contribute to solve the problem of natural balance. Glass waste is an alternative for ceramic glazing. This study employs experimental method with scientifically accountable structured and recorded exploration of data through experiments of glass waste for effective and efficient glazing material. It is expected that this research will contribute to the development of science among traditional ceramic artisans and other ceramic producers to result in creative and innovative glass-based media of expression.It is also expected that this study will motivate the society to have better concern on glass waste as well as excite creativity and innovation resulting in new attractive design of glass-waste glazed ceramics with higher competitiveness in the global market. Key words: glass waste, glazing, ceramic